“Caixa do diabo” : representações construídas pela Assembléia de Deus de Salvador sobre a televisão (1960-2000) - Santana, Lucas Gomes (2013)
The Assemblies of God in Brazil keep the image a traditional Pentecostal Denomination.This traditionalism is evidenced in rigid patterns of practices and customs advocated by the group with the aim of indoctrination of the faithful and in order to maintain cohesion and also maintaining an image of morality and detachment from sin, according to the understanding of the same. These standards relate to prohibitions, especially the clothes, the haircut, the consumption of alcoholic beverages and the use and ownership of television. This dissertation examines how the leaders of the Assembly God in Brazil and the Bahia created representations about television, in the period from 1960 to 2000, and which mechanisms of meaning construction did with that the denomination, which had an attitude refractory to the use and ownership of television, becomes tenant schedules in TV networks and andcompasse his own TV network, "Rede Boas Novas".